Study of Metal-complexes of 5-substituted Uracils - Mishra, A.P. (Asian Journal of Chemistry, 2010)
The Electrochromatographic method, i.e. novel ionophoretic technique, has been employed in quite modified way, after several improvements. The method is based upon the migration of a metal ion spot on the chromatographic paper strip soaked with ligand added background electrolyte, under electrical influence. Ionophoretic mobilities were recorded at different pH's of background electrolyte (containing ligand viz. 5-methyluracil/5-aminouracil/5-bromouracil) and a plot mobility vs. pH was drawn for information on the formation of metal-complex and calculation of equilibrium constant values for Hg(II) and Be(II) ions at I ═ 0.1 & temp. 35 ± 0.1ºC.